2020
DOI: 10.1038/s41431-020-0611-2
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to donate genomic and other medical data: results from Germany

Abstract: This paper reports findings from Germany-based participants in the "Your DNA, Your Say" study, a collaborative effort among researchers in more than 20 countries across the world to explore public attitudes, values and opinions towards willingness to donate genomic and other personal data for use by others. Based on a representative sample of German residents (n = 1506) who completed the German-language version of the survey, we found that views of genetic exceptionalism were less prevalent in the German-langu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 17 publications
4
31
0
Order By: Relevance
“…Upon comparison, similar surveys from other countries demonstrate higher rates: with 86% in Italy [ 7 ], 86% in Sweden [ 8 ], 83.5% in Korea [ 9 ], 70.4% in Germany [ 10 ]. Others show similar rates: with 56% in Germany [ 11 ], and 54% in the US [ 12 ]. At the same time, a global survey of 36,268 respondents across 22 countries indicated that willingness to donate data to doctors, and non-profit and for-profit researchers, was generally “low” (47.4%), with variation among countries (from 29% in Japan up to 63.7% in Mexico) [ 13 ].…”
Section: Discussionmentioning
confidence: 93%
“…Upon comparison, similar surveys from other countries demonstrate higher rates: with 86% in Italy [ 7 ], 86% in Sweden [ 8 ], 83.5% in Korea [ 9 ], 70.4% in Germany [ 10 ]. Others show similar rates: with 56% in Germany [ 11 ], and 54% in the US [ 12 ]. At the same time, a global survey of 36,268 respondents across 22 countries indicated that willingness to donate data to doctors, and non-profit and for-profit researchers, was generally “low” (47.4%), with variation among countries (from 29% in Japan up to 63.7% in Mexico) [ 13 ].…”
Section: Discussionmentioning
confidence: 93%
“…One reason for this might be that the early perception as a surveillance tool for authorities left many people reluctant to use contact tracing apps. The observed tendency to put these contact tracing apps into a broader context of technological surveillance tools and privacy concerns might have triggered general concerns of privacy that are known to be particularly important in the German-speaking areas [ 70 ], and the same has been reported in the French context [ 18 ]. Newspapers reporting the use of contact tracing and tracking apps in Asian countries might have further deepened the impression that these applications are not aligned with democratic principles of individual privacy and freedom since these applications were considered by interview participants and newspapers alike to be not compatible with privacy regulations and democratic principles as understood in the European context.…”
Section: Discussionmentioning
confidence: 99%
“…In the survey ‘Your DNA, Your Say’, 52% of the participants from the USA, UK, Canada and Australia held this point of view 25 . German participants holding an exceptionalist position argued that the genome is unique, is the most personal information of individuals and belongs to them 29 . Furthermore, a recent qualitative study indicated that participants consider genomic data as exceptional not because of an inherent difference, but merely because of its uses outside of health care and its familial implications 8…”
Section: Discussionmentioning
confidence: 99%
“…For example, when asked about their motivation to participate in genomic research, participants from several studies mentioned both benefits for their health and the health of their relatives, their descendants and the global population 8‐23 . While some participants in earlier studies highlighted the perception of the genome as a common good by referring to altruism, solidarity and even responsibility as citizens and human beings, 8‐29 other participants emphasized an individualistic understanding of the genome by referring to concepts such as reciprocity, respect for an individual's autonomy, 29 informed consent, 7,8 transparency and being up‐to‐date on the uses of their data and new genetic results 20‐23 …”
Section: Discussionmentioning
confidence: 99%